THE PLACE AND ROLE OF PSYCHOLOGICAL TRAINING FOR MILITARY SERVANTS - Lieutenant Colonel Egamov Elnur Eson ugli (Web of Journals Publishing, 2024)
This article describes the theoretical foundations and recommendations for the formation of professional flexibility skills of future military personnel, as well as the role and role of psychological training for military personnel.
Keywords: military serviceman, professional flexibility, skills, training, physical activity.